The government as a large shareholder: Impact on firm value and corporate governance - Marcelo Fernandes; Walter Novaes (Queen Mary University of London, School of Economics and Finance, 2015)
The subprime crisis led to a wave of government interventions in the private sector that has been particularly strong in Europe and Latin America, where several governments are large shareholders in a variety of public firms. In a sense, the subprime crisis induced these governments to behave as active large shareholders. This paper uses a sample of public firms in Brazil to show that government activism lowers the value of minority shareholders' voting rights. While the corporate governance literature usually associates lower voting premia with stronger protection of minority shareholders, we provide evidence that the government-induced decline in the value of voting rights harmed minority shareholders in Brazil.
Keywords: G14; G18; G30; G38; 330; Interventionism; Monitoring; Private benefits; Voting premium